(untitled) - Joseph JáJá (Massachusetts, 1992)
Introduction; Basic techniques; Searching, merging, and sorting; Graphs; Planar geometry; Strings; Arithmetic computations; Randomized algorithms; Limitations of prams.
Keywords: computer algorithms,parallel processing ( electronic computer )